Politico-Theological Debates in Ghadames between the 1770s and the 1850s from a Global Perspective - Kerem Duymus (Afriques)
This article aims to shed light on the history of politico-theological debates in Ghadames, focusing on two distinct case studies through discourse analysis. The particular geographical location of Ghadames, situated between two prominent states—Morocco and the Ottoman Empire—each with their respective caliphal claims, has historically enabled the scholars of the city to formulate and substantiate their own political stances. As a result, a substantial body of written materials, including chronicles, biographies, and letters, has emerged from Ghadames, reflecting the political discourse as articulated by its scholars, who adapted their perspectives in response to shifts in regional power dynamics. Notably, this adaptation was facilitated by the active intellectual engagement of the city’s scholars. In this context, the article investigates the politico-theological discussions in Ghadames from the 1750s to the 1850s, analysing the persistent yet varied arguments and justifications, as well as the intellectual milieu that intersected with them.